A Science Education for Textural Creation and Iconic Forms of Infrastructure at Medan - Gamal Kartono; Mesra Mesra; Zulkifli Zulkifli; Barli Kifli (Jurnal Penelitian Pendidikan IPA, 2023)
Medan City, as the center of the Deli Malay Sultanate and the colonial administration in the past, boasts numerous iconic forms. The distinctive characteristics of these iconic forms hold significant potential for development as references in creating contextual texture painting art. Unfortunately, this potential remains largely unexplored. Therefore, this research aims to explore the potential of iconic forms in Medan City with the goal of developing them as references for the creation of textural painting art as a tourism product for Medan City. This study employs a descriptive qualitative approach, conducted both in the field and in the studio. The methods employed include surveys and creative creation, applying Graham Wallas' theory of creativity. Research data is collected from various sources using relevant techniques, subjected to data triangulation, and analyzed following an interactive model: data reduction and presentation, verification, and drawing conclusions. The research results indicate that the potential of iconic forms as references for abstract textural painting art emerges from their representation of Medan City's character, alongside the dynamic nature they embody. The exploration of abstract textural art becomes tangible during the painting process, which, in this study, involves deformative processes, particularly simplification and stylization. Abstract textural painting art is explored based on the principles of visual art and tourist art, resulting in artworks that possess both aesthetic and technical qualities as tourism products.